Ties between steppe and peninsula: Comparative perspective of the Bronze and Early Iron Ages of Мongolia and Кorea - Gantulga, Jamiyan-Ombo (Proceedings of the Mongolian Academy of Sciences, 2020)
This article describes the results of a comparative study of some monuments (settlement, dolmen, rock art) and some artifacts (pottery, arrowhead, dagger, bronze mirror, bead, whetstone) of the Bronze and Early Iron Ages of Mongolian steppe and Korean Peninsula. The comparative study sought to clarify the external and internal structures of the monuments, as well as the burial practices. In the case of artifacts, their materials and functions were considered.